2021
DOI: 10.1002/aocs.12491
|View full text |Cite
|
Sign up to set email alerts
|

Application of seed oils and its bioactive compounds in sunscreen formulations

Abstract: The photoprotective skincare products are in high demand to meet the consumer market with concern on skin health. Seed oils are commonly used as ingredients in many cosmetic products due to their natural antioxidants and now being increasingly recognized for their effects on skin health and photoprotection. This article briefly reviews the application of seed oils in sunscreen development focusing on the antioxidants that contribute to photoprotection, thus preventing UV-induced erythema and photoaging. The ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 100 publications
0
6
0
1
Order By: Relevance
“…FucoPol was used to prepare emulsions with four different oils commonly used in cosmetic products' formulations, namely, castor oil [35][36][37][38], paraffin oil [39][40][41], almond oil [42,43] and olive oil [44][45][46][47][48]. Castor oil is a natural oil that acts as an antimicrobial, anti-inflammatory, antioxidant, wound healing, vasoconstrictive [49] and UV-protective agent [50].…”
Section: Preparation Of Fucopol-stabilized Emulsions With Different Oilsmentioning
confidence: 99%
“…FucoPol was used to prepare emulsions with four different oils commonly used in cosmetic products' formulations, namely, castor oil [35][36][37][38], paraffin oil [39][40][41], almond oil [42,43] and olive oil [44][45][46][47][48]. Castor oil is a natural oil that acts as an antimicrobial, anti-inflammatory, antioxidant, wound healing, vasoconstrictive [49] and UV-protective agent [50].…”
Section: Preparation Of Fucopol-stabilized Emulsions With Different Oilsmentioning
confidence: 99%
“…An advantage to the use of GSO in cosmetic formulations is that natural products commonly have fewer undesirable effects when compared to synthetic ones (4). Furthermore, the oil contains compounds with great antioxidant activity (16). The combination of antioxidant activity of the GSO components with UVB filter octyl methoxycinnamate in emulsified formulations represents a strategy to protect the human skin against UV-induced damage.…”
Section: + 1591 • Omc (L) + 8921 • Gso (L) • Omc (L) R² = 090mentioning
confidence: 99%
“…Since the grape seed oil (GSO) is rich in bioactive compounds it has great potential application in pharmaceutical and cosmetic industry (13). This oil present high content of monounsaturated fatty acids (90%), such as linoleic acid (58-78% w/w), oleic acid (12-28% w/w) and antioxidants such as tannins, phenolic compounds and tocopherol (vitamin E) (14,15) which are capable of improving UV protection and epidermal antioxidant activity responsible for premature aging and photoaging (16). Chu et al (2021) (16) published a review article about the use of seed oils in sunscreen formulations, and the studies demonstrated that GSO inhibits lipid oxidation and ROSinduced damage and has anti-inflammation properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, seeds and the oil extracted from them contain interesting bioactive compounds such as tocopherols, phytosterols, phenolic compounds, carotenoids, and essential unsaturated fatty acids such as linolenic acid (omega‐3) and linoleic acid (omega‐6) (Cervera‐Mata et al., 2021; Chaves et al., 2020; Mushtaq et al., 2020). The nutraceutical, cosmetic, pharmaceutical, and food applications as well as the health effects of these compounds from different seed sources have been extensively studied and reviewed (Alexandre et al., 2017; Chu & Nyam, 2021; Ismail et al., 2019; Manca et al., 2020; Maqsood et al., 2020; Punia & Kumar, 2021; Quintin et al., 2019; Rakariyatham et al., 2020; Rodrigues et al., 2015). Although soybean, sunflower, rapeseed, cottonseed, and peanut constitute the oilseeds with the highest production around the world (USDA, 2022), a great variety of oilseeds are regionally produced constituting not only important incomes for local economies but also available resources for the food production chain.…”
Section: Introductionmentioning
confidence: 99%